2020
DOI: 10.1097/ftd.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Opioid and Stimulant Exposure In Utero Through Targeted and Untargeted Metabolomics Analysis of Umbilical Cords

Abstract: Background: Neonatal abstinence syndrome is an array of signs and symptoms experienced by a newborn due to abrupt discontinuation of intrauterine exposure to certain drugs, primarily opioids. In the United States, the incidence of neonatal abstinence syndrome has tripled over the past decade. The current standard of care for drug testing includes the analysis of infant urine and meconium. Sample collection is associated with several limitations, including diaper media interferences, limited sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Extracted samples were run on an AB SCIEX 3200 triple quadrupole mass spectrometer in negative ionization mode using previously published methods [ 17 , 18 , 19 ]. Change values for DHA and EPA were calculated between timepoints by subtracting 16-week concentrations from 36-week concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Extracted samples were run on an AB SCIEX 3200 triple quadrupole mass spectrometer in negative ionization mode using previously published methods [ 17 , 18 , 19 ]. Change values for DHA and EPA were calculated between timepoints by subtracting 16-week concentrations from 36-week concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Several experimental studies have shown that the umbilical cord is an excellent matrix for the isolation of opioids, with the identification of codeine, morphine, and 6 AM. However, at the same time, they have not found identification of some synthetic opioids [ 9 , 10 , 11 , 12 ]. Another experimental study conducted by Colmenero et al used different biological matrices, such as maternal hair, meconium, the umbilical cord, and the placenta, to research opioids and other drugs.…”
Section: Biological Matricesmentioning
confidence: 99%